Timing of complications following elective craniotomies - Claassens, Caren (Department of Anaesthesia and Perioperative Medicine, 2022)
Background: Conservative prolonged observation periods after elective craniotomies with admission to neurosurgical higher or intensive care units (ICU) have been the norm for many decades. This practice is neither evidence based nor a cost-effective use of medical resources. This observational audit aimed to establish the incidence and timing of serious complications after elective craniotomies in a low-middle income country context. Methods: The medical records of adult patients who had elective craniotomies for the 2-year period of March 2016-February 2018 at Groote Schuur Hospital were reviewed. Complication incidence and timing was analysed in all patients admitted to either the neurosurgical high care unit (HCU) or ICU post-operatively for the initial 24hr period. The specific complications in our audit was defined as: a decrease in Glascow Coma Scale (GCS) of more than 2 points from the preoperative baseline score, new onset or worsening motor deficit, seizures, diabetes insipidus, haemodynamic instability, severe hypertension, tracheal intubation or noninvasive ventilatory support, and death. Statistical analysis was primarily descriptive. Results: A total of 189 elective craniotomy patients were included in our audit for the 2-year period mentioned. In this study 37/189 (19.6%) patients developed 1 or more major complications during the initial 24 hr post-operative period. Of these 37 patients, 31 (83.8% [95% CI 71.9-95.7]) patients developed their first onset complication within six hours of admission to the HCU or ICU, and the remaining 6 (16.2% [95% CI 4.3-28.1]) in the subsequent 18 hours. All patients who developed life threatening complications (airway, ventilation or haemodynamic support) had their first onset complication (“red flag”) within six hrs of admission. Conclusion: Our audit suggests that consideration should be given to discharge patients to a general neurosurgical ward after an uncomplicated six hour postoperative ICU stay. While a significant amount of first onset complications may occur if a patient is discharged to the neurosurgical ward after this time period, these complications were unlikely to be immediately life threatening and should not require more than standard neurosurgical ward observations to detect.